Women and Politics in Paraíba, Brazil: Participation, Learning, and Empowerment - Pessoa de Carvalho; Maria Eulina; Rabay Glória (Adult Education Research Conference, 1999)
Life histories of pioneer female politicians illustrate instances of learning and empowerment within gender cultures and imbalance in private and public life. After transforming their personal and family lives, independent female candidates face greater obstacles located in the political and economic structure.